2011
DOI: 10.1186/1756-9966-30-15
|View full text |Cite
|
Sign up to set email alerts
|

Enhancive effects of Lewis y antigen on CD44-mediated adhesion and spreading of human ovarian cancer cell line RMG-I

Abstract: BackgroundThis study aimed to investigate the molecular structural relationship between cell adhesive molecule CD44 and Lewis y antigen, and determine the effects of Lewis y antigen on CD44-mediated adhesion and spreading of ovarian cancer cell line RMG-I and the Lewis y antigen-overexpressed cell line RMG-I-H.MethodsThe expression of CD44 in RMG-I and RMG-I-H cells before and after treatment of Lewis y monoclonal antibody was detected by immunocytochemistry; the expression of Lewis y antigen and CD44 was dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 26 publications
0
30
0
Order By: Relevance
“…Lewis y antigen is not only a part of the integrin α5β1 and αvβ3 structures, but is also a part of the structure of other adhesion molecules such as CD44 [19]. Therefore, increased expression of Lewis y antigen can improve the adhesion of cells to the matrix and promote cell adhesion and metastasis through corresponding signal transduction pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Lewis y antigen is not only a part of the integrin α5β1 and αvβ3 structures, but is also a part of the structure of other adhesion molecules such as CD44 [19]. Therefore, increased expression of Lewis y antigen can improve the adhesion of cells to the matrix and promote cell adhesion and metastasis through corresponding signal transduction pathways.…”
Section: Discussionmentioning
confidence: 99%
“…CD44, a CSC marker in HNSCC, plays a role in tumor metastasis [33]. CD44 is a cell-surface glycoprotein that functions as a receptor for hyaluronic acid and is involved in cell adhesion and migration [34]. In HNSCC, a subpopulation of CD44 + CSCs displays a phenotypic switch, and become either proliferative or migratory [35].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies found that an upregulated expression of the Lewis y antigen can increase the expression of CD44, α5β1 and αvβ3. The Lewis y antigen, a structural component of CD44, α5β1 and αvβ3, increases cell adhesion and chemoresistance through various signaling pathways [6,26]. The Lewis y antigen, an important structural component of many molecules, can increase the invasiveness, adhesion and anti-apoptotic nature of cancer cells, leading to an increased chemoresistance.…”
Section: Discussionmentioning
confidence: 99%